PENGARUH REGULASI DIRI TERHADAP KEAKTIFAN BELAJAR SISWA DI SMA N 1 MUARO JAMBI - Putri Tri Rizki; Akmal Sutja; Zubaidah Zubaidah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
This research was motivated by initial findings at SMA N 1 Muaro Jambi, which revealed that some students were disengaged in the learning process. Indicators of low engagement included not paying attention to the teacher, being passive during Q&A sessions, avoiding reading materials, and talking to friends while the teacher was explaining. This disengagement is linked to low self-regulation, or the ability to manage behavior, emotions, and motivation. Strong self-regulation helps students set clear learning goals and boosts intrinsic motivation, leading to greater involvement in learning. The aim of this study was to determine the effect of self-regulation on students’ learning engagement at SMA N 1 Muaro Jambi. This quantitative research used an ex post facto method. The study involved 1,105 students, with a sample of 294 selected using Slovin's formula and simple random sampling. Data were collected using a questionnaire, and analyses included percentage analysis, normality and linearity tests, and simple regression analysis.The study results indicate that self-regulation is categorized as high, with a percentage of 67.86%, while learning engagement also falls in the high category, with a percentage of 68.59%. The contribution of the self-regulation to the learning engagement, based on the R Square value, is 0.258 or 25.8%, which is classified as moderately strong. The T-test shows that the calculated t-value is 10.073, which is greater than the critical t-value of 1.960 at a 0.05 significance level, indicating that self-regulation significantly influences students' engagement in learning.